Complications with remediation strategies involving the biodegradation and detoxification of recalcitrant contaminant aromatic hydrocarbons - Frenzel, M.; Scarlett, Alan; Rowland, S.; Galloway, T.; Burton, S.; Lappin-Scott, H.; Booth, A. (Elsevier, 2010)
Environmentally persistent aromatic hydrocarbons known as unresolved complex mixtures (UCMs) derived from crude oil can be accumulated by, and elicit toxicological responses in, marine organisms (e.g. mussels, Mytilus edulis). Comprehensive two-dimensional gas chromatography time-of-flight mass-spectrometry (GC×GC-ToF-MS) previously revealed that these UCMs included highly branched alkylated aromatic hydrocarbons. Here, the effects of biodegradation on the toxicity and chemical composition of an aromatic UCM hydrocarbon fraction isolated from Tia Juana Pesado (TJP) crude oil were examined. 48h exposure of mussels to the aromatic hydrocarbon fraction (F2) resulted in tissue concentrations of 900µgg-1 (dry wt.) and ~45% decrease in clearance rate. Over 90% of the hydrocarbon burden corresponded to an UCM. Following a 5day recovery period, GC×GC-ToF-MS analysis of the tissues indicated depuration of most accumulated hydrocarbons and clearance rates returned to those observed in controls. To assess the potential of biodegradation to reduce UCM toxicity, TJP F2 was exposed to bacteria isolated from Whitley Bay, UK, for 46days. Mussels exposed to the undegraded TJP F2 from the abiotic control exhibited a reduction in clearance rate comparable with values for the pure crude oil TJP F2. Clearance rates of mussels exposed to biodegraded TJP F2 were statistically similar to seawater controls, suggesting biodegradation had reduced the TJP F2 toxicity. GC×GC-ToF-MS analysis revealed the same compound groups in the tissue of mussels exposed to pure TJP F2, undegraded TJP F2 and biodegraded TJP F2 samples; however >300 fewer compounds were observed in the biodegraded (954 compounds) compared to the undegraded TJP F2 (1261). The compound distributions were markedly different, possibly accounting for the decrease in toxicity. Extraction and analysis of pelleted bacterial cell material revealed that a significant proportion of the TJP F2 had adsorbed onto the cells. Thus extreme care must be taken in interpreting biodegradation data from recalcitrant UCM hydrocarbons. © 2010 Elsevier B.V.